Ways To Increase the Effectiveness of Physical Education Classes in Secondary Schools (Texas Journal of Multidisciplinary Studies, 2021)
This article discusses the importance of physical education in the development of physically strong, healthy, strong-willed and spiritually active children, physical education classes with students at school and ways and means to increase their effectiveness.